New products management - Crawford, C. Merle (McGraw - Hill, 2006)
New Products Management, 8/e, by Crawford and Di Bennedetto provides future new product managers, project managers and team leaders with a comprehensive overview of the new product development process including how to develop an effective development strategy, manage cross-functional teams across the organization, generate and evaluate concepts, manage the technical development of a product, develop the marketing plan, and manage the financial aspects of a project.